Evaluating the Challenges of Peasant Operators and its Effects on Rural Development with Structural Equations Approach (Case study: Zanjan Province, Iran) - zoleiha naderkhani; Yousef Ghanbari (جغرافیا و توسعه, 2023)
The aim of the research, which was carried out with a combination of descriptive-analytical methods, is to investigate the challenges of peasant operators and the effects of these challenges on the rural development of Zanjan province. In addition to library studies, a survey method has been used to collect the required data. The statistical population of the research is 75831 farmers located in Zanjan province, using Cochran's formula, 340 people have been estimated as a statistical sample. And to analyze the collected data, relevant tests and SPSS, AMOSE and GIS software have been used. The results of the research showed that economic challenges are the most important problems of farmers in the province, and the average number of challenges faced by farmers is 3.79, which is significantly higher than the average. The results of the analysis of variance test showed that there is a statistically significant difference among the cities of the province in terms of the challenges faced by the operators, and the cities of Soltanieh, Ijroud and Mahenshan with an average rank of 3.967, 3.864 and 3.651 have the highest and Khodabande, Abhar and Zanjan with an average rating of 3.347, 3.429 and 3.481 have the lowest number of challenges in peasant operators. Also, the overall situation of rural development with an average of 2.26 is significantly lower than the base average, and among its indicators, two key indicators of rural development, management and economy, are in a worse condition. The results of the final model of the research regarding the effects of the challenges faced by peasant operators on rural development, whose fit was finally confirmed, showed that social and environmental challenges with coefficients of -0.67 and -0.26, respectively, have the highest and lowest have had a negative effect on rural development.